(untitled) (Research, Society and Development, 2020)
To analyze the development of actions aimed at health care in the home environment with a focus on patient safety. This is an integrative literature review carried out from the SCIELO, LILACS and BDENF databases. The search for publications for the period from 2005 to 2018 was refined, with a critical analysis of the studies found through the narrative synthesis. The PICO strategy was used to elaborate the guiding question: how is nursing care organized in the home environment to promote safe care? 16 articles were selected for interpretation, discussion and composition of this study. Thus, two categories were defined for the discussion of results: prevention of risks and damage in care provided at home; and nursing and patient safety in the home environment. The study demonstrated that nursing professionals have a fundamental role in establishing patient safety at home, insofar as they become responsible for carrying out the main interventions necessary during the treatment of the individual at home.